1997
DOI: 10.1149/1.1837577
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Photoelectron Spectroscopic Examinations of Electrochemically Formed Passive Layers on Ni‐Cr Alloys

Abstract: The structure and composition of passive films electrochemically formed on Ni-Cr alloys in 1 M NaOH and 0.5 M H7S04 has been studied with x-ray photoelectron spectroscopy. The passivation potential was varied within the passive range up to the transpassive range and the time of passivation from 10 ms to 1000 s. With angular-resolved x-ray photoelectron spectroscopy, the passive film was found to have a two-layer structure with an inner oxide part formed directly at the metal surface and an outer hydroxide part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
44
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 5 publications
(6 reference statements)
10
44
0
Order By: Relevance
“…The presence of chromium in the electrode was only noticeable on the i/E st found by other authors in X-rays photoelectron spectroscopy (XPS) examinations of the electrochemically formed passive layers on Ni-Cr alloys [16]. They found that the XPS analysis of the passive layer formed at a potential range from -1.0 V to 0.0 V showed that Ni(II) and Cr(III) oxides and hydroxides were developed.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The presence of chromium in the electrode was only noticeable on the i/E st found by other authors in X-rays photoelectron spectroscopy (XPS) examinations of the electrochemically formed passive layers on Ni-Cr alloys [16]. They found that the XPS analysis of the passive layer formed at a potential range from -1.0 V to 0.0 V showed that Ni(II) and Cr(III) oxides and hydroxides were developed.…”
Section: Resultsmentioning
confidence: 88%
“…They suggested a two-layer model for the passive layers formed at Ni-Cr (80:20) alloy electrodes, an inner oxide layer in contact with the metal and an outer hydroxide layer in contact with the electrolyte. The XPS data showed that Ni(OH) 2 and Cr(OH) 3 are present in the outer hydroxide layer, Ni(III) and some soluble Cr(VI) are only observed in the transpassive potential range [16]. Only the redox couple Ni(II)/Ni(III) was observed on the i/E voltammetric trace at a potential range from 0.0 V to 0.6 V.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations